2009
DOI: 10.1002/chem.200902025
|View full text |Cite
|
Sign up to set email alerts
|

Mode‐Selective Electrical Excitation of a Molecular Rotor

Abstract: Einfaches Schalten: Ein verdrillter Möbius‐aromatischer [28]Hexaphyrin‐PdII‐Komplex und ein planarer Hückel‐aromatischer [26]Hexaphyrin‐PdII‐Komplex lassen sich mithilfe einer neuartigen Palladiumwanderung bei Oxidation und Reduktion reversibel ineinander umwandeln. Der PdII‐Komplex ist eine Vorstufe für Heterodimetall‐[26]Hexaphyrin‐Komplexe mit einem PdII‐ und einem CuIII‐ oder AgIII‐Zentrum. C grau, N blau, H weiß, F grün, Pd gelb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…To date, the reported action spectra can be classified into four types according to their spectral shapes: single-mode excitation [8][9][10][11][12][13][14], multiple-mode excitation [4,[15][16][17][18][19][20][21], combination-mode excitation [19,21,22], and single-overtonemodeexcitation [12], as shownin Figs. 1(a)-1(d), respectively.…”
mentioning
confidence: 99%
“…To date, the reported action spectra can be classified into four types according to their spectral shapes: single-mode excitation [8][9][10][11][12][13][14], multiple-mode excitation [4,[15][16][17][18][19][20][21], combination-mode excitation [19,21,22], and single-overtonemodeexcitation [12], as shownin Figs. 1(a)-1(d), respectively.…”
mentioning
confidence: 99%
“…38 When to a static dibutyl sulfide molecule at 7 K a pulse of 0.7 V tunnelling electrons was delivered by the STM tip, it started to rotate. 38 When to a static dibutyl sulfide molecule at 7 K a pulse of 0.7 V tunnelling electrons was delivered by the STM tip, it started to rotate.…”
Section: Rotational Motionmentioning
confidence: 99%
“…As previously mentioned, temperature is a key factor for controlling the molecular motion, and many research groups have reported STM studies of temperature effects. For example, an isolated thioether anchored onto Au(111) rotated and was observed as a round feature at temperatures of 20–78 K [54,55,56]. At 7 K the molecular vibration was almost frozen and this feature appeared enlongated.…”
Section: Molecular Rotations In Arraysmentioning
confidence: 99%